Damaged Self-Esteem is Associated with Internalizing Problems - Creemers, Daan; Scholte, Ron; Engels, Rutger; Prinstein, Mitchell; Wiers, Reinout W. (Frontiers in Psychology, 2013)
Implicit and explicit self-esteem are assumed to be important factors in understanding the onset and maintenance of psychological problems. The current study aims to examine the association between implicit and explicit self-esteem and their interaction with depressive symptoms, suicidal ideation and loneliness. Specifically, the relationship between the size and the direction of the discrepancy between implicit and explicit self-esteem with depressive symptoms, suicidal ideation and loneliness were examined. Participants were 95 young female adults (M= 21.2 years, SD = 1.88) enrolled in higher education. We administered the IAT to assess implicit self-esteem, and the Rosenberg self-esteem scale to measure explicit self-esteem while psychological problems were assessed through self-reports. Results showed that discrepancies between implicit and explicit self-esteem were positively associated with depressive symptoms, suicidal ideation, and loneliness. In addition, the direction of the discrepancy was specifically relevant: damaged self-esteem (i.e., high implicit self-esteem and low explicit self-esteem) was consistently associated with increased levels of depressive symptoms, suicidal ideation, and loneliness. In contrast, defensive or fragile self-esteem (i.e., low implicit and high explicit self-esteem) was solely associated with loneliness. These findings provide further support that specifically damaged self-esteem is an important vulnerability marker for depressive symptoms, suicidal ideation, and loneliness.